Guest Editorial Introduction 客座主编介绍: Special Issue on International Student in China 来华留学生专刊 - Tian, Mei; Lu, Genshu (Journal of International Students, 2020)
In this special issue editorial, we firstly discuss the sharp contrast between the rich English literature on Chinese students overseas, and the limited studies published in international journals on international students in China. We then introduce the rapid expansion of international student enrolment in China in recent ten years, pointing to the significance and urgency to deepen our understandings of these students’ experiences. The editorial ends with an introduction to the contents of the articles included in the special issue. We hope that this issue on international students in China will motivate Chinese-speaking researchers in and outside China to contribute to this important research area.  本文首先讨论了海外针对中国留学生经历的究热情，指出目前发表在国际期刊上的围绕来华留学生经历的研究还十分有限，二者形成了鲜明的对比。随后介绍了来华留学生近年来的发展与增长趋势，反映出深入研究来华留学生经历、来华留学生教育的重要性与紧迫性。最后介绍了收录在本辑特刊中的文章内容。我们希望可以以《国际学生杂志》中文特刊为契机，鼓励更多的中国本土与海外学者贡献于这一重要的研究领域。